CESAR - Cost-efficient Methods and Processes for Safety-relevant Embedded Systems - Rajan, Ajitha; Wahl, Thomas; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
The book summarizes the findings and contributions of the European ARTEMIS project, CESAR, for improving and enabling interoperability of methods, tools, and processes to meet the demands in embedded systems development across four domains - avionics, automotive, automation, and rail. The contributions give insight to an improved engineering and safety process life-cycle for the development of safety critical systems. They present new concept of engineering tools integration platform to improve the development of safety critical embedded systems and illustrate capacity of this framework for end-user instantiation to specific domain needs and processes. They also advance state-of-the-art in component-based development as well as component and system validation and verification, with tool support. And finally they describe industry relevant evaluated processes and methods especially designed for the embedded systems sector as well as easy adoptable common interoperability principles for software tool integration.
The CESAR concept -- The system design life cycle -- Requirements engineering -- Architecture exploration -- Component-based development -- Interoperability -- The reference technology platform -- Implementation of the RTP -- Interoperability -- Evaluation of CESAR: pilot applications -- CESAR results.
Keywords: Engineering; Mechanical engineering; Industrial engineering; Systems engineering; Engineering; Industrial and Production Engineering; Mechanical Engineering; Circuits and Systems